GOTONG ROYONG DI PROVINSI JAWA TENGAH SEBAGAI SISTEM SOSIAL BUDAYA DALAM KEHIDUPAN MASYARAKAT INDONESIA - Yunita, Melysia; Putri, Silvi (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Mutual cooperation is a very basic local wisdom culture.Wich is the foundation of Indonesia society. This articel aims to find out more about the existence of mutual cooperation which has become a social system that continues and is relevant in the context of community life in Indonesia. In the literature study method, this study will analyze the historical, sociological, and cultural dimensions of the practice of mutual cooperation. Mutual cooperation has undergone social changes due to modernization and globalization. Although some traditional activities have shifted, with the basic principles of solidarity and mutual assistance to maintain mutual cooperation activities as an important role in building relationships between residents and in solving social problems. In theory. Clifford Geertz, an anthropologist from America has conducted in-depth research in Indonesia, which has provided an interesting comparative view. In his book entitled